The impact of pay comparisons on effort behavior - Daniele Nosenzo (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2010)
This study uses a three-person gift-exchange game experiment to examine the impact of pay comparisons on effort behavior. We compare effort choices made in a treatment where workers' wages are secret with effort choices made in two 'public wages' treatments. The two 'public wages' treatments differ in whether co-workers' wages are chosen by an employer, or are fixed exogenously by the experimenter. We find that pay comparison information has an overall detrimental impact on effort choices: employees respond less favorably to the wage offers made by the employer when they receive information about the wage paid to the co-worker as compared to the case where co-workers' wages are secret. These effects are particularly pronounced in the treatment where the level of the co-worker's wage is fixed exogenously.
Keywords: C91; C92; J31; 330; social comparisons; wage comparisons; gift exchange; experiments; Ökonomischer Anreiz; Lohn; Vergleich; Verhalten; Test